A novel chromatic confocal one-shot 3D measurement system based on DMD. (December 2021) - Yu, Qing; Zhang, Yali; Zhang, Yi; Cheng, Fang; Shang, Wenjian; Wang, Yin
Highlights: DMD is used as a beam splitter in the chromatic confocal system. The full-field measurement can be realized by one-shot 3D photography. A mathematic model was established to correlate the height of each point on the target surface with the color information. Abstract: Aiming at the problem of low measurement efficiency of conventional single-point chromatic confocal technology, a one-shot chromatic confocal measurement system based on DMD (Digital Micromirror Device) is presented in this paper. This system was set up by applying a polychromatic light source, a color camera, a dispersive lens, and DMD. Firstly, the DMD was used to modulate the polychromatic light source to obtain a point light array. Secondly, a series of focal points were generated by the dispersive lens, and the corresponding relationship between color information and height was established. Lastly, by using an optimized HSI model, the height information of the sample could be obtained, and a 3D profile could be reconstructed accordingly. The experimental data showed that the proposed system can measure and restore the 3D topography of the measured surface by one-shot photography, and the measurement accuracy can reach the micron level.